Detection and control problems for non-linear distributed-parameter systems with delays - Namir, Abdelwahed; Lahmidi, Fouad; Labriji, Elhoussine (Zielona Góra: Uniwersytet Zielonogórski)
First, we consider non-linear discrete-time and continuous-time systems with unknown inputs. The problem of reconstructing an input using the information given by an output equation is investigated. Then we examine a control problem for non-linear discrete-time hereditary systems, i.e. the problem of finding a control which drives the state of the system from its initial value to a given desired final state.
Keywords: distributed parameter systems; non-linear discrete-time systems; detection; control; fixed-point theorems